Network scanner / Anisyahayati Ismail - Anisyahayati, Ismail (2005)
This report is submitted for WXES3182, an academic axercise which is required for final year students of the faculty of computer science and information technology who will be graduating. The Network Scanner is a program that is developed to provide information on the network vulnerabilities especially open service port so that network security actions can be performed earlier. A lot of researches have been done in order for me to understand the basics of network scanning and what information it provides. From the researches, I have gained a lot of information regarding the purpose of the network scanner, its functions, techniques that have been used in network scanning and a little insight of the design process of a network scanner. Finally I have completed developing the Network Scanner project. Although this project is not much compared to the current Network Scanners in the market, I still hope that this Network Scanner will bring knowledge to other people like it did to me. This course should be maintained for students as it actually encourage students to implement the knowledge they have acquired during the minimum of six semesters of studies in the faculty.